Ostrom and the commons: Critical appreciation and interrogation in the context of forest management in Tanzania. Issue 127 (January 2022) - Perfect-Mrema, Joseph
Abstract: This article is inspired by renewed interest in scholarship of the commons. It offers critical appreciation and interrogation of Ostrom (1990) design principles (DPs) that are well-cited in academic circles. The article departs from numerous studies that analyse robustness of common property institutions (CPR) institutions according to the presence/absence of the DPs to offer finer description of how the DPs are put into practice and implemented overtime. In-depth longitudinal data that inform this article was collected from the pioneering and supposedly best case of Community Based Forest Management (CBFM) in Tanzania. The analysis of the quality of design and functionality of the DPs overtime indicate six DPs are partially fulfilled, two DPs are hardly fulfilled and no any DP is either totally unfulfilled (not visible at all) or fully fulfilled. The institutional inadequacies related to several DPs – i.e. boundaries, rules, collective action arrangements, conflict resolution and nested enterprises- and their relationships and cumulative impacts contribute towards unsustainable outcomes. The latter is evidenced by decrease in closed woodlands by 114.3 ha per year and 452.7 ha per year during and after phase-out donor funded programme respectively. As such, there is good association between very much undermined DPs after phase out of donor funded programme and quadrupled rate of deforestation. The policy implications of these findings are put forward. Highlights: This article offers description of the quality of design and functionality of Ostrom (1990) design principles (DPs) overtime. The studied case is the pioneering and supposedly best case of Community Based Forest Management (CBFM) in Tanzania. Findings indicate no DP is fully unfulfilled or fulfilled, six DPs are partially fulfilled and two DPs are hardly fulfilled. The established inadequacies related to several DPs and their cumulative impacts contribute towards unsustainable outcomes. Quadrupled rate of deforestation is associated with very much undermined DPs after phase out of donor funded programme.